The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1002/ijc.11484
|View full text |Cite
|
Sign up to set email alerts
|

Single amino acid substitutions in the transmembrane domains of breast cancer resistance protein (BCRP) alter cross resistance patterns in transfectants

Abstract: doxorubicin Certain members of ABC transporters such as the MDR1 gene product P-gp and MRP1 are involved in the anticancer drug resistance of tumor cells. 1-3 Such transporters pump out various structurally unrelated antitumor agents in an ATP-dependent manner. BCRP, also called ABCG2, ABCP or MXR, is a member of ABC transporters that has an N-terminal ATP binding domain and a C-terminal TM. 4 -6 BCRP is speculated to function as an S-S homodimer. 7 BCRP overexpression has been reported in various drug-res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 19 publications
5
78
0
Order By: Relevance
“…Docking calculations indicate that Arg 482 directly interacts with mitoxantrone and Hoechst33342, but not with prazosin and SN-38 (86). This is consistent with previous findings that resistance to mitoxantrone was increased, but resistance to SN-38 or efflux of prazosin was not affected, by mutations of Arg 482 (16,87). This also is in agreement with the studies showing that prazosin binds to a site that does not fully overlap with that for mitoxantrone or Hoechst33342 (88) and the binding of a prazosin derivative to BCRP was relatively unaffected by mutations of Arg 482 (89).…”
Section: Structure Determination and Homology Modelingsupporting
confidence: 90%
“…Docking calculations indicate that Arg 482 directly interacts with mitoxantrone and Hoechst33342, but not with prazosin and SN-38 (86). This is consistent with previous findings that resistance to mitoxantrone was increased, but resistance to SN-38 or efflux of prazosin was not affected, by mutations of Arg 482 (16,87). This also is in agreement with the studies showing that prazosin binds to a site that does not fully overlap with that for mitoxantrone or Hoechst33342 (88) and the binding of a prazosin derivative to BCRP was relatively unaffected by mutations of Arg 482 (89).…”
Section: Structure Determination and Homology Modelingsupporting
confidence: 90%
“…The R482T and R482G are BCRP variants identified after in vitro selection of culture cells and these variants confer DOX-and MXR-resistances. (34) Before examining the suppressive effect of sunitinib on these BCRP variant-expressing murine fibroblast PA317 cells, cell populations with high BCRP expression were selectively enriched using immunomagnetic beads. The BCRP protein expression levels were confirmed to be comparable between each enriched variant BCRP-expressing PA317 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The anti-BCRP polyclonal antibody 3488 was generated as described elsewhere. (34) Cells and drug sensitivity assay. PA317 mouse fibroblast cells, K562 human myelogenous leukemia cells, BCRP-expressing PA317 cells, BCRP-expressing K562 cells (K562 ⁄ BCRP), and P-gp-expressing K562 cells (K562 ⁄ MDR) were established and cultured as previously.…”
Section: Methodsmentioning
confidence: 99%
“…s0090 4.2.1 Role of the R482 position p0375 It turned out very early, practically at the cloning of ABCG2 that R482 is a crucial determinant of substrate recognition of ABCG2. In these early studies, it was found that a mutation of R482 to G or T occurred in the cell lines upon anthracycline selection, most probably because these "artificial" (not occurring in vivo) mutant ABCG2 variants results in a "gain-of-function" transporter with increased doxorubicin and rhodamine 123 transport activity (Chen et al, 2003;Honjo et al, 2001;Miwa et al, 2003;Ozvegy, Varadi, & Sarkadi, 2002). Later it turned out that amino acid 482 is also involved in the cholesterol and bile acid sensing of the protein.…”
Section: Article In Pressmentioning
confidence: 99%